2023
DOI: 10.1002/jaba.1052
|View full text |Cite
|
Sign up to set email alerts
|

Multiple schedules of conjugate reinforcement and extinction: A translational model for assessing automatically reinforced behavior

Matthew C. Peterson,
Patrick M. Ghezzi,
John T. Rapp

Abstract: This study evaluated the extent to which a conjugate reinforcement schedule (CONJ) involving a contingency between pedaling a stationary bike and viewing a preferred movie could serve as a translational preparation for the analysis of automatically reinforced behavior. In part, researchers examined whether providing participants with either an accurate or an inaccurate rule about the extinction (EXT) component of a multiple schedule (MULT) contributed to the development of control by the MULT (CONJ EXT) schedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Recently, researchers have developed dynamic conjugate preparations for translational (e.g., Davis et al, 2021;Falligant et al, 2018Falligant et al, , 2020MacAleese et al, 2015;Peterson et al, 2024) and applied (Curiel et al, 2023;Deochand et al, 2020;Diaz de Villegas et al, 2020;McHugh et al, 2022) studies. Briefly summarized, results from MacAleese et al (2015), Curiel et al, 2023;Falligant et al (2018Falligant et al ( , 2020, and Deochand et al (2020) illustrate how (a) behavior under conjugate schedules changes reliably to various auditory and visual stimulus events and (b) extinction of conjugately reinforced behavior gives rise to dynamic changes in response rate and response force.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, researchers have developed dynamic conjugate preparations for translational (e.g., Davis et al, 2021;Falligant et al, 2018Falligant et al, , 2020MacAleese et al, 2015;Peterson et al, 2024) and applied (Curiel et al, 2023;Deochand et al, 2020;Diaz de Villegas et al, 2020;McHugh et al, 2022) studies. Briefly summarized, results from MacAleese et al (2015), Curiel et al, 2023;Falligant et al (2018Falligant et al ( , 2020, and Deochand et al (2020) illustrate how (a) behavior under conjugate schedules changes reliably to various auditory and visual stimulus events and (b) extinction of conjugately reinforced behavior gives rise to dynamic changes in response rate and response force.…”
mentioning
confidence: 99%
“…Several studies have evaluated conjugate arrangements in the context of operant assessments; that is, researchers provided auditory stimulation as a consequence in either a conjugate schedule (Falligant et al, 2018(Falligant et al, , 2020Peterson et al, 2024;Saunders et al, 2001) or a conjugate variation, such as a synchronous schedule (e.g., Diaz de Villegas et al, 2020;Leslie et al, 2023;McHugh et al, 2022). To our knowledge, no study has evaluated a brief conjugate preparation for identifying relative preference for music using response force as the primary dimensional measure.…”
mentioning
confidence: 99%
“…For example, when an individual pedals a bicycle, the speed at which the bicycle moves and the corresponding visual and proprioceptive stimulus change are directly proportional to the force that individual applies to the pedals. Since Lindsley's (1956Lindsley's ( , 1957 original conjugate preparations, researchers have fashioned a variety of simple and dynamic conjugate preparations to (a) examine the motor development of infants (Rovee & Rovee, 1969;Siqueland & Delucia, 1969), (b) increase social therapeutic behavior in adults (Lindsley, 1963;Nathan et al, 1964Nathan et al, , 1968), (c) increase exercise behavior (Caouette & Reid, 1991;Deochand et al, 2020), and (d) assess stereotypical behavior of individuals with intellectual disabilities (Peterson et al, 2024;Rapp et al, 2004;Switzky & Haywood, 1973).…”
mentioning
confidence: 99%
“…Several applied and translational studies have shown the potential of synchronous and conjugate schedules for evaluating stimulus preference and the efficacy of those stimuli to serve as reinforcers (Cook et al, 2024;Curiel et al, 2024;Davis et al, 2021;Diaz de Villegas et al, 2020;Falligant et al, 2018Falligant et al, , 2020MacAleese et al, 2015;Peterson et al, 2024; see also Pel aez-Nogueras et al, 1996). Davis et al (2021) used a conjugate preparation to measure 54 college students' preferences for pictorial stimuli.…”
mentioning
confidence: 99%